2018
DOI: 10.1371/journal.pgen.1007799
|View full text |Cite
|
Sign up to set email alerts
|

Genetic regulation of the placental transcriptome underlies birth weight and risk of childhood obesity

Abstract: GWAS identified variants associated with birth weight (BW), childhood obesity (CO) and childhood BMI (CBMI), and placenta is a critical organ for fetal development and postnatal health. We examined the role of placental transcriptome and eQTLs in mediating the genetic causes for BW, CO and CBMI, and applied integrative analysis (Colocalization and MetaXcan). GWAS loci associated with BW, CO, and CBMI were substantially enriched for placenta eQTLs (6.76, 4.83 and 2.26 folds, respectively). Importantly, compared… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
56
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(57 citation statements)
references
References 31 publications
1
56
0
Order By: Relevance
“…Placental transcript profiling in birth cohorts with comprehensive longitudinal follow-up of the children may also potentially uncover new placental programming mechanisms that can influence extrauterine life in the longer term. Indeed, previously identified placental eQTLs were predictive of birthweight and subsequent childhood obesity in a cohort study, highlighting the role of placental gene expression in modulating postnatal outcomes, and such genes could serve as potential molecular targets for interventions ( Peng et al , 2018 ). Besides profiling more placentas from additional birth cohorts, it is of great interest to examine currently available birth cohort-related placental transcriptome datasets for any possible associations with childhood outcomes ( Binder et al , 2015 ; Cox et al , 2019 ).…”
Section: Knowledge Gaps and Future Directionsmentioning
confidence: 99%
“…Placental transcript profiling in birth cohorts with comprehensive longitudinal follow-up of the children may also potentially uncover new placental programming mechanisms that can influence extrauterine life in the longer term. Indeed, previously identified placental eQTLs were predictive of birthweight and subsequent childhood obesity in a cohort study, highlighting the role of placental gene expression in modulating postnatal outcomes, and such genes could serve as potential molecular targets for interventions ( Peng et al , 2018 ). Besides profiling more placentas from additional birth cohorts, it is of great interest to examine currently available birth cohort-related placental transcriptome datasets for any possible associations with childhood outcomes ( Binder et al , 2015 ; Cox et al , 2019 ).…”
Section: Knowledge Gaps and Future Directionsmentioning
confidence: 99%
“…38 Molecular studies could include the placental transcriptome for genetic variants of gene expression (eQTLs) that predict childhood obesity and BMI. 39 Epigenomic methylation of DNA and histones should be monitored across the lifespan of the infant. DNA methylation measures represented as epigenetic clocks that represent "aging" can be estimated in pediatric and then adult years.…”
Section: Neonatal Outcomesmentioning
confidence: 99%
“…A SNP intronic in ITPR2 (chr12:26958660, hg19) has been reported to be cis-eQTL with ITPR2 in human placenta [43]. A recent study found that rs12812999, a SNP in strong linkage disequilibrium (LD) (r 2 = 0.94) with the birthweight GWAS lead SNP rs2306547, influences ITPR2 transcript levels in placenta [44].…”
Section: Plos Geneticsmentioning
confidence: 99%
“…that found decreased expression of ITPR1 in skeletal muscle of aged mice [44], and association of placental epigenetic age acceleration with fetal growth [36]. A more direct way to assess the mechanism is first to identify the intrauterine factor influenced by rs746039, and then examine the relationship between the putative intrauterine factor and ITPR1 expression.…”
Section: Plos Geneticsmentioning
confidence: 99%